Demographic and Socio-Economic Factorts as Determinants of Tax Complaince in Self-Assessment System (Sas) In Akwa Ibom State, Nigeria - Umoffong, Nsima Johnson; Etim, Etim Osim; Bassey, Daniel Okon (Archives of Business Research, 2020)
The study examined three determinants of voluntary compliance in self-assessment system of tax administration in Akwa Ibom State, Nigeria. This was motivated by the growing need to increase tax revenues generation in developing countries the tax revenue as a ratio of Gross Domestic Product is below the global average and tax administration machinery has been ineffective. Data for the study were collected using a structured questionnaire from respondents registered with the state Board of Internal Revenue determined using Taro Yamene’s Statistical Formula. Descriptive and Regression Analyses were adopted for data treatment. The model summary reveals that 80.8% of the variation in Tax compliance is accounted for the variables of perception of equity and fairness, income level and level of education of the tax payers. The ANOVA Summary justifies that the independent variables have significant influence on tax compliance with f-calculated value of 233.763 being greater than the critical f-value of 0.308451 at P<0.05. The regression coefficient indicates a positive and significant relationship between perception of equity and fairness (0.260), level of education (0.103) and tax compliance. Income level (-0.055) has negative influence on tax compliance. It is recommended that tax authorities should evolve a framework that will motivate, control, sensitize and educate tax payers on voluntary compliance in Self-Assessment system.